Developing Differentiated e-LKPD Products: A TPACK Approach for Grade X/Fase E - Efendi, Rachmat; Sakti, Norida Canda; Sudarwanto, Tri (SAINTIS Publishing, 2024)
This study aims to develop e-LKPD (Electronic Student Worksheets) products integrated with the TPACK (Technological, Pedagogical, and Content Knowledge) approach for Grade X/E Phase as part of the implementation of the Kurikulum Merdeka. The research employs the 4D development model, which includes the phases of define, design, develop, and disseminate. The define phase identifies instructional needs, while the design phase produces an e-LKPD design focused on differentiated learning. During the develop phase, the product is validated by experts using assessment sheets for content, media, and language aspects. The disseminate phase involves sharing links to enhance the visibility of the research product. Expert validation results indicate excellent feasibility ratings: 91% for media, 96% for content, and 95% for language. These findings confirm that the developed e-LKPD is effective and ready for classroom implementation. The product not only enhances student learning outcomes but also fosters inclusive participation and critical thinking. This study makes a significant contribution to the advancement of educational technology and instructional design, providing a valuable resource for educators in implementing innovative teaching strategies.